Absorbent incontinence pad use and the association with urinary tract infection and frailty: A retrospective cohort study - Emma Bendix Larsen; Caroline Lunne Fahnøe; Peter Errboe Jensen; Merete Gregersen (Elsevier, 2023)
Background: Up to 40% of adults over 65 years are full-time users of absorbent incontinence pads due to urinary incontinence. Simultaneously, urinary tract infection is amongst the most common hospital-acquired infection in older patients. Objectives: To explore the association between (1) full-time use of absorbent incontinence pads and urinary tract infection at acute hospital admission, (2) state of frailty and becoming a pad user during hospitalization, and (3) becoming a pad user and acquiring a urinary tract infection during hospitalization in older patients. Design: A retrospective cohort study. Setting: Admissions in an emergency department with transfers to geriatric, cardiac, infectious, or endocrinological wards from September 7th, 2017 to February 18th, 2019. Patients: 1,958 patients aged 65 years or more, having daily homecare or moderate comorbidity, hospitalized due to acute illness, and living in the municipality of Aarhus. Methods: The study was conducted by two researchers reviewing the patients' electronic health records combined with data on frailty status from a geriatric quality database. In the electronic health records, data on baseline characteristics, absorbent incontinence pad use at admission and during the hospital stay, and urinary tract infection were obtained. Results: Full-time users of absorbent incontinence pads had a higher probability of being admitted with urinary tract infection (Odds Ratio=2.00 (95% Confidence Interval: 1.61-2.49); p<.001). Patients identified as severely frail had a higher probability of becoming pad users during hospitalization (Odds Ratio=1.57 (95% Confidence Interval: 1.45-1.71); p<.001) compared to non/mild/moderate frail patients. Patients who became pad users during hospitalization had a higher risk of a hospital-acquired urinary tract infection (Odds Ratio=4.28 (95% Confidence Interval: 1.92-9.52); p<.001). Conclusions: There was an association between the use of absorbent incontinence pads and the development of urinary tract infections in older hospitalized patients, both in full-time users and those who were frail and became pad users during hospitalization. These findings emphasize the need for further research on preventing urinary tract infections and unnecessary pad use in older patients.